Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social

Why Music Matters - Hesmondhalgh, David (John Wiley & Sons, 2013)
Listen to David Hesmondhalgh discuss the arguments at the core of 'Why Music Matters' with Laurie Taylor on BBC Radio 4's Thinking Allowed here. In what ways might music enrich the lives of people and of societies? What prevents it from doing so? Why Music Matters explores the role of music in our lives, and investigates the social and political significance of music in modern societies. First book of its kind to explore music through a variety of theories and approaches and unite these theories using one authoritative voice Combines a broad yet theoretically sophisticated approach to music and society with real clarity and accessibility A historically and sociologically informed understanding of music in relation to questions of social power and inequality By drawing on both popular and academic talk about a range of musical forms and practices, readers will engage with a wide musical terrain and a wealth of case studies
Keywords: Music / General; Music / History & Criticism

The Lost Women of Rock Music: Female Musicians of the Punk Era - Reddington, Helen (Equinox Pub., 2012)
In the late 1970s and early 1980s a new phenomenon emerged in UK popular music - female guitarists, bass-players, keyboard-players and drummers began playing in bands. Before this time, women's presence in rock bands, with a few notable exceptions, had always been as vocalists. This sudden influx of female musicians into the male domain of rock music was brought about by the enabling ethic of punk rock ('anybody can do it ') and by the impact of the Sex Discrimination Act. With the demise of the punk scene, interest in these musicians evaporated and other priorities became important to music audiences. This book investigates the social and commercial reasons why these women became lost from the rock music record, and rewrites this period of popular music history. In addition to a wealth of original interview material with key protagonists, including the late John Peel, Geoff Travis, The Raincoats and Poison Girls, this new edition has been updated to include interviews with members of Birmingham-based band The Au Pairs, Leeds-based band Delta 5 and Viv Albertine of The Slits. Lucy Whitman (aka Lucy Toothpaste), who started the fanzine Jolt and later wrote for Spare Rib, also provides enlightening words on the relationship between female punk band members and feminism. The author also draws on her own experience as bass-player in a punk band.
Keywords: Music / Genres & Styles / Punk; Music / History & Criticism; Social Science / Women's Studies

The Sex Revolts: Gender, Rebellion, and Rock 'n' Roll - Reynolds, Simon; Press, Joy (Harvard University Press, 1996)
Iggy Pop once said of women: "However close they come I'll always pull the rug from under them. That's where my music is made." For so long, rock 'n' roll has been fueled by this fear and loathing of the feminine. The first book to look at rock rebellion through the lens of gender, The Sex Revolts captures the paradox at rock's dark heart--the music is often most thrilling when it is most misogynist and macho. And, looking at music made by female artists, it asks: must it always be this way?Provocative and passionately argued, the book walks the edgy line between a rock fan's excitement and a critic's awareness of the music's murky undercurrents. Here are the angry young men like the Stones and Sex Pistols, cutting free from home and mother; here are the warriors and crusaders, The Clash, Public Enemy, and U2 taking refuge in a brotherhood-in-arms; and here are the would-be supermen, with their man-machine fantasies and delusions of grandeur, from Led Zeppelin and Jim Morrison to Nick Cave and gangsta rap. The authors unravel the mystical, back-to-the-womb longings of the psychedelic tradition, from Pink Floyd, Jimi Hendrix, and Van Morrison to Brian Eno, My Bloody Valentine, and ambient techno. Alongside the story of male rock, The Sex Revolts traces the secret history of female rebellion in rock: the masquerade and mystique of Kate Bush, Siouxie, and Grace Jones, the demystifiers of femininity, like the Slits and Riot Grrl, tomboy rockers like L7 and P. J. Harvey, and confessional artists like Janis Joplin, Joni Mitchell, and Courtney Love.A heady blend of music criticism, cultural studies, and gender theory by two of rock's keenest observers, The Sex Revolts is set to become the key text in the women-in-rock debate.
Keywords: Music / History & Criticism